2016
DOI: 10.1530/joe-16-0105
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in IVF in women of advanced age

Abstract: Women above age 40 years in the US now represent the most rapidly growing age group having children. Patients undergoing in vitro fertilization (IVF) are rapidly aging in parallel. Especially where egg donations are legal, donation cycles, therefore, multiply more rapidly than autologous IVF cycles. The donor oocytes, however, are hardly ever a preferred patient choice. Since with use of own eggs, live birth rates decline with advancing age but remain stable (and higher) with donor eggs, older patients always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
40
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 13 publications
2
40
0
8
Order By: Relevance
“…Delayed marriage and childbearing have become global phenomena because of concerns regarding lifestyle in developed countries, and advanced age is the most detrimental factor affecting the establishment of conception . Numerous studies have indicated that fertility rates begin to gradually decline at the age of 30, with greater declines by age 35 and substantial declines by age 40 . Providing effective treatment over a short‐time period is a major challenge for all gynecologists engaging in infertility treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed marriage and childbearing have become global phenomena because of concerns regarding lifestyle in developed countries, and advanced age is the most detrimental factor affecting the establishment of conception . Numerous studies have indicated that fertility rates begin to gradually decline at the age of 30, with greater declines by age 35 and substantial declines by age 40 . Providing effective treatment over a short‐time period is a major challenge for all gynecologists engaging in infertility treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Aging is the most important factor in reproductive health; fertility and the live birth rate of individuals who undergo in vitro fertilization (IVF) cycles are reduced with aging, especially in those older than 35 years of age . One study in which oocyte donation/recipient cycles were investigated indicated that oocyte quality, rather than the uterine environment, plays a crucial role in IVF outcomes among aged infertile women .…”
Section: Introductionmentioning
confidence: 99%
“…Неудивительно, что на данный момент сохраняется тенденция обращения женщин позднего репродуктивного возраста по поводу лечения бесплодия, учитывая, что реализация репродуктивной функции с возрастом имеет ряд сложностей. Основные причины снижения эффективности программ вспомогательных репродуктивных технологий (ВРТ) в данной группе пациенток условно можно разделить на «ооцит-независимые» и «ооцит-зависимые» [3].…”
unclassified
“…К «ооцит-независимым» факторам относятся отягощенный гинекологический или соматический анамнез. Имплантация эмбриона, децидуальная трансформация и плацентация напрямую зависят от состояния эндометрия [3]. Доказана роль гипоксических процессов в эндометрии женщин старшего репродуктивного возраста, в связи с чем наблюдается тенденция к компенсаторной плацентарной гипертрофии [4].…”
unclassified
See 1 more Smart Citation